2015
DOI: 10.1038/oncsis.2015.10
|View full text |Cite
|
Sign up to set email alerts
|

Human dCTP pyrophosphatase 1 promotes breast cancer cell growth and stemness through the modulation on 5-methyl-dCTP metabolism and global hypomethylation

Abstract: Human DCTPP1 (dCTP pyrophosphatase 1), also known as XTP3-transactivated protein A, belongs to MazG-like nucleoside triphosphate pyrophosphatase (NTP-PPase) superfamily. Being a newly identified pyrophosphatase, its relevance to tumorigenesis and the mechanisms are not well investigated. In the present study, we have confirmed our previous study that DCTPP1 was significantly hyperexpressed in breast cancer and further demonstrated its strong association with tumor progression and poor prognosis in breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 62 publications
4
46
2
Order By: Relevance
“…The expressions of DCTPP1 and MDR1 in GC tissue microarray were tested by immunohistochemistry described in our previous report using anti-DCTPP1 and anti-MDR1 antibodies [21]. Slides were observed under the light microscope and data were analyzed using the Leica Qwin V3 image analysis system (Leica Microsystems GmbH, Wetzlar, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The expressions of DCTPP1 and MDR1 in GC tissue microarray were tested by immunohistochemistry described in our previous report using anti-DCTPP1 and anti-MDR1 antibodies [21]. Slides were observed under the light microscope and data were analyzed using the Leica Qwin V3 image analysis system (Leica Microsystems GmbH, Wetzlar, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…HEK293T cell line was used to demonstrate we could immunolabel BMX (van Oosterwijk et al , ) and VGLL4 (Jiao et al , ), but only showed a moderate cytoplasmic expression of BMX and were negative for VGLL4; weak immunolabelling of survivin was also detected. The K562 cell line was used to demonstrate the immunolabelling of DCTPP1 (Song et al , ) and survivin (Schmidt et al , ), and showed moderate cytoplasmic levels of both. MDA‐MB‐231 cell line was used to demonstrate we could immunolabel DCTPP1 (Song et al , ), while MDA‐MB‐468 was chosen as an immunolabelling control for VGLL4 (Zhang et al , ), but both were negative for the detection of these antigens.…”
Section: Resultsmentioning
confidence: 99%
“…The K562 cell line was used to demonstrate the immunolabelling of DCTPP1 (Song et al , ) and survivin (Schmidt et al , ), and showed moderate cytoplasmic levels of both. MDA‐MB‐231 cell line was used to demonstrate we could immunolabel DCTPP1 (Song et al , ), while MDA‐MB‐468 was chosen as an immunolabelling control for VGLL4 (Zhang et al , ), but both were negative for the detection of these antigens. Of note VGLL4 was not found in any cell line, MDA‐MB‐231 and MDA‐MB‐468 did not express DCTPP1 or survivin, while each had transcripts from these antigens that were detectable by qPCR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] It catalyzes the hydrolysis of dNTPs to their corresponding monophosphates and displays higher affinity towards 5-modified non-canonical dNTPs (e.g., 5-I-dCTP > 5-Br-dCTP > 5-Me-dCTP > dCTP), thereby decreasing their intracellular levels and hence subsequently their insertion into nascent DNAd uring replication. [9,10] dCTPP1 is considered an attractive anticancer target, because it is overexpressed in many carcinomas (e.g.,b reast and gastric). [11] Reversible binding of dCTPP1 to probe 2 was confirmed by means of concentration-dependent competitive pull-down using immunoblotting for dCTPP1 ( Figure 2b).…”
mentioning
confidence: 99%